Pengaruh Bauran Pemasaran Jasa Terhadap Loyalitas Anggota Di KPN PEMKO Padang - Muthi’ah Muthi’ah; Marwan Marwan (EKONOMIKA45 : Jurnal Ilmiah Manajemen, Ekonomi Bisnis, Kewirausahaan, 2022)
The research problem is the low, low member loyality at KPN PEMKO Padang, low service marketing at KPN PEMKO Padang. The purpose of this research is to determine the effect of product, price, promotion, place, physical evidence, people, processes, productivity and quality of member loyalty in KPN PEMKO Padang. The research method is causative research, causative research is research that is useful for analyzing the relationship between one variable and another or how one variable affects other variables. The research is product, price, promotion, physical evidence, people, process, productivity and quality have a positive and significant effect on member loyalty in KPN PEMKO Padang and place does not have a positive and significant effect on member loyalty in KPN PEMKO Padang. The conclusion of the study is that there is a positive influence and sign If product, price, promotion, physical evidence, people, process, productivity and quality affect the loyalty of members at KPN PEMKO Padang, there is no significant effect on the place variable on member loyalty at KPN PEMKO Padang.